Reconstructing Human Nature in the Merdeka Curriculum: A Philosophical-Anthropological Inquiry - Irvan Herlambang; Kholifah, Zahrah Luthfi; Adinda Innayah P.l; Yuventio Dwi Arampan; Lia Febria Kurnianingsih; Nandang Budiman (Journal of Practice Learning and Educational Development, 2026)
The rapid transformation of Indonesia's educational system has raised concerns about curricula that prioritize measurable outcomes and technical skills, often neglecting the deeper dimensions of human identity. This qualitative study aims to reconstruct the concept of human nature as the ontological, anthropological, and philosophical foundation for developing the Merdeka Curriculum in Indonesia. Employing a critical library research approach, this study analyzes philosophical and anthropological perspectives on education alongside policy documents related to the Merdeka Curriculum. The findings indicate that the Merdeka Curriculum possesses significant humanistic potential through its emphasis on learner autonomy, differentiated instruction, and character development as articulated in the Pancasila Student Profile. However, tensions persist between industrial demands and the vision of education as a humanization process. This research underscores the importance of grounding curriculum development in a holistic understanding of human nature to ensure education nurtures learners comprehensively.